Boosting the electrical and mechanical properties of structural dielectric capacitor composites via gold nanoparticle doping. (1st December 2019) - Chan, Kit-Ying; Yang, Dan; Demir, Baris; Mouritz, Adrian P.; Lin, Han; Jia, Baohua; Lau, Kin-Tak
Abstract: Structural dielectric capacitors (SDCs) are load-bearing multifunctional materials that uniquely combine high electrical energy storage capacity with high mechanical properties. The development of electrically conductive carbon fibre reinforced polymer (CFRP)-based electrodes is a promising approach to create high strength SDCs, although challenges remain due to the low conductivity of epoxy matrix of CFRP. Carbon nanotubes and graphene nanoplatelets are commonly used as conductive fillers to produce electrically conductive polymers. However, the electrical conductivity of composites is restricted by the maximum filler content, which is essential to retain composite structures. In this work, gold nanoparticles (AuNPs) with high electrical conductivity were added in different weight fractions (up to 1 wt%) into the epoxy matrix of CFRP electrodes used in graphene oxide-bearing SDCs (GO/SDCs). The electrical conductivity of AuNP-modified CFRP electrodes was 15–250% higher than the unmodified CFRP electrode, depending on the concentration of nanoparticles. As a result, both specific capacitance and energy storage density of AuNPs-modified GO/SDCs were higher (up to 170% and 50%, respectively) than the unmodified GO/SDC. Furthermore, AuNP-modified GO/SDCs had higher tensile and interlaminar shear properties. This research provides new insights into improving both the electrical and mechanical properties of SDCs using AuNPs.